Factors affecting formaldehyde emission in particleboard manufacturing / Mohd Zahid Jaafar - Jaafar, Mohd Zahid (Faculty of Applied Sciences, 2016)
The aim of this study was to identify the formaldehyde emission release in manufacturing industry by using rubber wood, tropical wood and mixed wood. Type of resin that was used in this process was SEO, EO and E1. This study divided into two test which were emission release and mechanical testing. In a formaldehyde emission testing there were used perforator and desiccator compared to mechanical strength using instron machine. From the result showed that tropical wood have a smallest number of formaldehyde emission compared to others. In mechanical testing tropical wood also have a greater strength followed by mixed wood and rubber wood.